2018
DOI: 10.3390/ijms19113539
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Transcriptional Activity of Forkhead Box O1 by Histone Deacetylase Inhibitors Ameliorates Hyperglycemia in Type 2 Diabetic Rats

Abstract: Type 2 diabetes mellitus (T2DM) is a chronic disease manifested by hyperglycemia. It is essential to effectively control hyperglycemia to prevent complications of T2DM. Here, we hypothesize that repression of transcriptional activity of forkhead box O1 (FoxO1) via histone deacetylase inhibitors (HDACi) ameliorates hyperglycemia in T2DM rats. Methods: Male Long-Evans Tokushima Otsuka (LETO) and Otsuka Long-Evans Tokushima Fatty (OLETF) rats aged 14 weeks were administered sodium valproate (VPA, 0.71% w/v) disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…We could replicate in our studies data from other groups which have previously shown that the inhibition of class IIa HDACs reduces the expression of genes regulating gluconeogenesis ( 24 , 26 , 41 ). Initially, we confirmed these effects of our siRNAs in vitro in human primary hepatocytes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We could replicate in our studies data from other groups which have previously shown that the inhibition of class IIa HDACs reduces the expression of genes regulating gluconeogenesis ( 24 , 26 , 41 ). Initially, we confirmed these effects of our siRNAs in vitro in human primary hepatocytes.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, this is the same treatment group in which also HDAC3 was decreased. A previous study demonstrated that both, HDAC3 and 4 isoforms interact with the transcription factor FOXO1 and that a simultaneous knockdown of HDAC3 and 4 attenuates its localization to gluconeogenic gene promoters ( 24 , 26 ). Consistently, deficiency of FOXO1 resulted in a decrease in hepatic glucose production and reduced hyperglycemia in type 2 diabetic rats ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors and coactivators such as FOXO1 [ 215 , 216 ], FOXO3a [ 151 ], and PGC-1 α [ 217 ] are induced. Complexly, HDAC inhibitors can also lead to increased acetylation of FOXO1, which reduces its activity at the promoters of genes for gluconeogenic enzymes in the liver to decrease blood glucose levels [ 218 ]. This is likely beneficial for inhibiting the cytokine storm as discussed above.…”
Section: Molecular Mechanisms Through Which R-bhb Restores Redox Bmentioning
confidence: 99%
“…The application of VPA as an HDACI extends to other disease areas. For example, recent studies have found that VPA inhibits HDAC in different isoforms as an antidote for attenuating renal fibrosis and type 2 diabetes [ 93 , 94 ].…”
Section: Application Of the Epigenetic Effect Of Antiepileptic Drugsmentioning
confidence: 99%